2014
DOI: 10.1002/pip.2498
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of enhanced chlorine segregation at grain boundaries in polycrystalline CdTe thin films via three‐dimensional TOF‐SIMS imaging

Abstract: For more than 25 years, the CdTe photovoltaic research and manufacturing communities have been subjecting CdTe materials to a CdCl 2 treatment or activation step to improve performance. However, little work has been carried out using imaging to elucidate the spatial distribution of chlorine in the CdTe devices after this treatment. This work addresses fundamental questions about the spatial distribution of chlorine in the CdTe absorber material after a CdCl 2 treatment comparable to industrial practices. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…There is also an increase in the chlorine counts within the CdS compared with the CdTe, as is often observed for CdCl 2 -treated cells10. This is at least in part due to the change in matrix upon sputtering from the CdTe into the CdS: the sputter yield of chlorine from the two materials is different and this acts to increase the count rate from CdS11 rather than indicating a genuine increase in concentration. In contrast, both the NaCl and KCl treatments give only a minor increase in the chlorine concentration, and even then this is confined to the CdTe nearest to the diffusion surface—deeper in the CdTe, the chloride level does not rise above its background value.…”
Section: Resultsmentioning
confidence: 80%
“…There is also an increase in the chlorine counts within the CdS compared with the CdTe, as is often observed for CdCl 2 -treated cells10. This is at least in part due to the change in matrix upon sputtering from the CdTe into the CdS: the sputter yield of chlorine from the two materials is different and this acts to increase the count rate from CdS11 rather than indicating a genuine increase in concentration. In contrast, both the NaCl and KCl treatments give only a minor increase in the chlorine concentration, and even then this is confined to the CdTe nearest to the diffusion surface—deeper in the CdTe, the chloride level does not rise above its background value.…”
Section: Resultsmentioning
confidence: 80%
“…The positive effect of CdCb on minority-carrier lifetime is well known and anticipated to be due to the elimination of deep-level traps, particularly in the grain boundaries (GB) [II]. Recent studies have demonstrated a large concentration of chlorine near the GB, indicating its role in their passivation [12]. EELS profiling by Chen Li et al demonstrated Te reduction and CI enrichment while having same relative Cd concentration in the grain boundary [13].…”
Section: Results and Analysismentioning
confidence: 99%
“…The poor performance is mainly attributed to a low shunt resistance (282 Ω·cm 2 ), which is an indication of insufficient GB passivation. After the CdCl 2 treatment, which is known to incorporate Cl into CdTe and facilitate GB passivation [14], [15], the cell efficiency is improved to ∼14.2%. J SC is further increased to 26.4 mA/cm 2 , which is rather high for a CdTe cell with no ARC.…”
Section: B Solar Cell Performancementioning
confidence: 99%